Fundamentals of general, organic, and biological chemistry - Holum, John R. 4 0 16; 5 (New York : John Wiley & Sons, 1998)
A general chemistry text, exploring nature and human life at their molecular levels and providing an introduction to genetic engineering and the genetic code. Includes chapter summaries and practice and review exercises.
Includes indexes.
Adult;Adult
Keywords: 2 -- 0; 6; Chemistry.;Chemistry.; 20; 2